NEW PUBLICATION: Enhancing Climate Resilience in Nigerian Agriculture: Implications for Sustainable Adaptation and Livelihood Diversification - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
IFPRI Nigeria is pleased to announce the publication of Enhancing Climate Resilience in Nigerian Agriculture: Implications for Sustainable Adaptation and Livelihood Diversification by IFPRI researchers; Amare Mulubrhan, Balana Bedru, Onilogbo Omobolanle.